2018
DOI: 10.1093/jxb/ery206
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of strigolactones in regulating scion growth and branching in grafted grapevine in response to nitrogen availability

Abstract: Grapevine rootstocks regulate scion growth and architecture differently in response to nitrogen availability. Strigolactones are suggested as key root-derived molecules modulating scion development in grafted grapevine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…In woody plant, poplar MAX4 (CCD8) knockdown lines exhibited altered branching patterns [24]. In grape, it has been suggested that SL could be involved in the control of scion architecture in grafted grapevine plants, based on the observation that exudate from grape CCDs-overexpressing transgenic cells could stimulate the germination of Phelipanche ramosa seeds, and that overexpression of grape CCD7 or CCD8 gene in corresponding Arabidopsis mutant can partly revert the mutant phenotype [25]. However, no direct and clear evidence supporting this role exists in grapevine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In woody plant, poplar MAX4 (CCD8) knockdown lines exhibited altered branching patterns [24]. In grape, it has been suggested that SL could be involved in the control of scion architecture in grafted grapevine plants, based on the observation that exudate from grape CCDs-overexpressing transgenic cells could stimulate the germination of Phelipanche ramosa seeds, and that overexpression of grape CCD7 or CCD8 gene in corresponding Arabidopsis mutant can partly revert the mutant phenotype [25]. However, no direct and clear evidence supporting this role exists in grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SLs were proposed to control scion development in response to nitrogen availability in grafted grapevine plants [25]. Additionally, overexpression of grape CCD7 or CCD8 gene in Arabidopsis max3 or max4 mutants background partly reverted their phenotypes [25], suggesting a potential role for CCD7 and CCD8 in grapevine shoot branching. However, up to date, in grapevine no experimental evidence supporting the role of these two genes in the control of shoot branching exists.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on Pi (an inorganic form of phosphorus) reported that strigolactones can regulate root systems by improving development of lateral root formation with a suitable concentration of Pi and conversely inhibit the emergence of lateral roots with a high concentration of Pi. Thus, reducing the uptake of heavy metals in the plant by decreasing the length and density of root hairs is one of the avoidance mechanism of strigolactones for coping with heavy metals [95][96][97][98][99][100][101]. Recent research has confirmed the role of strigolactones (SLs) on the LR (latest root) formation process, which occurs in synthetic strigolactone stages [27].…”
Section: Strigolactones (Sls) Via Heavy Metal Stressmentioning
confidence: 99%
“…Exogenous GR24 leads to increasing plant tolerance against salt and drought stress in Arabidopsis . When placed in the root access, it is transferred to the shoots , creating a positive role in coping with stress [101]. A previous experiment found that GR24 reduced MDA content and chloroplast damage and increased the photosynthetic capacity and plant defense mechanism against ROS with the stimulation of antioxidant enzyme activity (SOD and POD) caused by salinity stresses [1].…”
Section: Strigolactones (Sls) Via Heavy Metal Stressmentioning
confidence: 99%
“…Several SL-driven developmental modules have been shown to be highly conserved in the plant kingdom, like shoot lateral branching, root hair elongation, leaf aging and crosstalk with most phytohormones. The recent development of SL-based strategies seems endless, going from approaches targeted to the improvement of good agricultural practices (Pavan et al, 2016; Cochetel et al, 2018; Liu et al, 2018a; Mohemed et al, 2018) to the amelioration of human health through the recently revealed apoptotic function of SL mimics in different kinds of cancers and diseases (Modi et al, 2017, 2018; Hasan et al, 2018).…”
Section: Abcg Subfamily and Strigolactone Transportmentioning
confidence: 99%